Z와 Statechart에 의한 열차제어시스템 바이탈 소프트웨어 개발 방법 분석 - 趙賢庭(Hyun-Jeong Jo); 黃宗奎(Jong-Gyu Hwang); 尹用基(Yong-Ki Yoon) (전기학회 논문지 P권, 57(2), 2008)
- Recently, many critical control systems are developed using formal methods. When software applied to such systems is developed, the employment of formal methods in the software requirements specification and verification will provide increased assurance for such applications. Earlier error of overlooked requirement specification can be detected using formal specification method. Also the testing and full verification to examine all reachable states using model checking to undertake formal verification are able to be completed. In this paper, we propose an eclectic approach to incorporate Z(Zed) formal language and ‘Statemate MAGNUM’ which is formal method tools using Statechart for applying to the railway signaling systems. KCI Citation Count: 0